Пошаговое объяснение:
1)2√5 - √125 + 3√80=2√5-√25*5+3√16*5=2√5-5√5+12√5=9√5
2) √6 × 7√54=√6*7√9*6=√6*7*3√6=21*6=126
3)(√162 - 10√2) × √2=√162*2-10√2*2=√324-10*2=18-20=-2
4)(√5 + √y) (√5 - √y)=(√5)²-(√y)²=5-y
5)(3√t - √k)²==(3√t)²-2*3√t*k+(√k)²=9t-6√tk+k
6)(√c - 5√d) (√d - √c)=√cd-5d-c+5√cd=6√cd-5d-c
Пошаговое объяснение:
1)2√5 - √125 + 3√80=2√5-√25*5+3√16*5=2√5-5√5+12√5=9√5
2) √6 × 7√54=√6*7√9*6=√6*7*3√6=21*6=126
3)(√162 - 10√2) × √2=√162*2-10√2*2=√324-10*2=18-20=-2
4)(√5 + √y) (√5 - √y)=(√5)²-(√y)²=5-y
5)(3√t - √k)²==(3√t)²-2*3√t*k+(√k)²=9t-6√tk+k
6)(√c - 5√d) (√d - √c)=√cd-5d-c+5√cd=6√cd-5d-c